2019
DOI: 10.5539/mas.v13n7p25
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Application of IT Governance According to (COBIT 5) Framework in Reduce Cloud Computing Risks

Abstract: The study aimed at identifying the impact of the application of IT governance represented by (Planning and Organization, Possessiveness and Implementation, Support and Delivery, Monitoring and Evaluation, and Guidance and Control), using (COBIT 5) framework to reduce the risks associated with cloud computing (Identity and Access Management, Data protection, Virtual operating risk, IT support, and Organization) in the Jordanian industrial companies public shareholding from the perspective of Jordanian Certified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
2
Order By: Relevance
“…There are many previous studies that dealt with the intellectual realities of the impact of IT governance (COBIT5), so we find the study of (Okour, 2019) that studied the impact of IT governance under COBIT5 framework on reducing the risks of cloud computing in Jordanian industrial companies, and to achieve the goals of this study, a Descriptive and analytical approach was used, The study community consisted of external certified public accountants practicing the auditing profession in Jordan, which numbered until the end of 2017 (384) as a practicing certified auditor, The study reached many results, the most important of which is the interest of the management of industrial companies in maximizing added value through the company's activities and operations and IT resources, and ensuring the optimal exploitation of it, and tightening control over the risks and threats of information technology. In addition to the efforts of the Jordanian industrial contributing companies to reduce the risks and threats generated by their use of technology and the extent of the efficiency and effectiveness of the procedures they follow in order to reduce those risks and reduce the size of their negative repercussions and the damage it causes to the company and its dealers, and to ensure The integrity and correctness of its data and information and maintaining it.…”
Section: Literature Reviewmentioning
confidence: 94%
“…There are many previous studies that dealt with the intellectual realities of the impact of IT governance (COBIT5), so we find the study of (Okour, 2019) that studied the impact of IT governance under COBIT5 framework on reducing the risks of cloud computing in Jordanian industrial companies, and to achieve the goals of this study, a Descriptive and analytical approach was used, The study community consisted of external certified public accountants practicing the auditing profession in Jordan, which numbered until the end of 2017 (384) as a practicing certified auditor, The study reached many results, the most important of which is the interest of the management of industrial companies in maximizing added value through the company's activities and operations and IT resources, and ensuring the optimal exploitation of it, and tightening control over the risks and threats of information technology. In addition to the efforts of the Jordanian industrial contributing companies to reduce the risks and threats generated by their use of technology and the extent of the efficiency and effectiveness of the procedures they follow in order to reduce those risks and reduce the size of their negative repercussions and the damage it causes to the company and its dealers, and to ensure The integrity and correctness of its data and information and maintaining it.…”
Section: Literature Reviewmentioning
confidence: 94%
“…As achieving pre-planned goals contributes to directing and controlling the organization, information technology governance is often used to promote desirable behaviors in the use of information technology (Putri et al, 2017). Accordingly, Okour (2019) focused on comparing a group of businesses that adopted IT governance mechanisms with the performance of their IT departments. According to Lunardi et al (2014), companies that implemented IT governance policies performed better than their competitors, especially in terms of making profits.…”
Section: Literature Review Developed the Hypothesismentioning
confidence: 99%
“…Effective corporate governance and the establishment of IT governance rely heavily on meticulous planning and organization (Okour, 2019). Effective organization and planning are necessary to ensure the successful implementation of IT management, where IT features are translated from the governance structure into tangible procedures and practices within the company (Patón-Romero et al, 2017).…”
Section: Planning and Organizing And Bank Performancementioning
confidence: 99%
“…When the coefficient is equal to 0.179, the t value is 3.761, and the sig t indicated that (GC) has a significant effect on Audit Risk, where coefficient equals (0.470) is significant with (t= 17.172) and (Sig t =0.000) less than 0.05. Okour (2019) discovered that effective guidance and control greatly reduce the risk associated with cloud computing. Several studies have identified IT competency use of guidance and control as an important factor influencing audit practices to improve auditing and reduce associated risk (Mazza & Azzali, 2018;Siew, Rosli, & Yeow 2020;Thottoli, 2021).…”
Section: Hypothesis Testmentioning
confidence: 99%